Investigation of the relationship between apical periodontitis and host modulation provided by nutritional supplement: a study in rats - Cankaya, Guzide; Ocak, Mevlut Sinan; Dundar, Serkan; Ozercan, Ibrahim Hanifi (Bmc, 2025)
BackgroundTraditional treatments often involve chemotherapeutic agents; however, immune modulation agents, such as probiotics, propolis, Vitamin E, and vegetable oils, may offer alternative approaches to reduce inflammation and bone damage. In this study, we aimed to investigate the effect of various host modulation agents (probiotics, propolis, Vitamin E, and vegetable oils) on inflammation and bone loss in a rat model of experimental apical periodontitis (AP). MethodsEight-week-old Sprague-Dawley rats (n = 79) were used. AP was induced by exposing the coronal pulp of the mandibular right first molar. Rats were divided into seven groups: Control, AP, AP + Vegetable Oil, AP + Probiotic, AP + Propolis, AP + Vitamin E, and AP + Physiological Serum. The host modulation agents were administered daily for 30 days. Serum calcium, phosphorus, and alkaline phosphatase levels were measured, along with histopathological and immunohistochemical evaluations. Statistical analyses were conducted using one-way ANOVA and Tukey's test (p < 0.05). ResultsVitamin E and vegetable oil significantly reduced inflammation by 33% and 28%, respectively, compared with the AP group (p < 0.0001 for both). Probiotics reduced fibrosis by 36% (p = 0.0002), and all agents except propolis showed lower serum calcium levels (p = 0.0017) than the AP group. Osteoblastic activity was higher in the AP and Vitamin E groups (p = 0.0366), whereas both propolis and vitamin E treatments resulted in a 20% reduction in osteoclastic activity (p = 0.0389). No significant effect on abscess formation was observed (p = 0.2610). Compared to the AP group, RANKL levels were significantly lower in the supplemented groups by 28-50% (p = 0.0036). ConclusionsSpecific nutritional supplements with host modulation effectively reduced inflammation and bone loss in experimental AP. These findings suggest the potential of these agents in improving endodontic treatment outcomes. Further studies are required to explore their clinical application.
Keywords: Apical periodontitis; Host modulation; Inflammation; Nutritional supplementation; Rat model